Implementation of Sharia-Based Money Changer System in PT. Hidayah Prima Valasindo - Syaharani, Jihan; Agustina, Ahadiah; Ariani, Zaenafi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The study assessed the implementation of a Sharia-based money changer system in PT. Hidayah Prima Valasindo focuses on the challenges faced in ensuring compliance with Sharia principles. The purpose of this study is to know if implementation is consistent with the principles of sharia. Several obstacles arise during implementation processes such as a lack of clarity in risk management policies, and staff un understanding of the Sharia principle. This type of research uses qualitative methods, and data collection techniques conducted by observation, interview, and documentary. The study suggests that companies on the implementation of systems in the company have not fully complied with the principles of the sharia. Such as a discrepancy in risk management policies that have not fully obeyed the sharia principles and there is a gap in staff’s understanding of the principles, especially in the application of the sharia principle in daily transactions. The research is a platform for the corrective measures needed to ensure full compliance and successful implementation of the Sharia-based money changer system in PT. Hidayah Prima Valasindo.